"Assessment of chronic sclerodermoid Graft‐versus‐Host Disease patients, using 20MHz high‐frequency ultrasonography and cutometer methods". Issue 1 (12th August 2012) - Osmola‐Mańkowska, Agnieszka; Silny, Wojciech; Dańczak‐Pazdrowska, Aleksandra; Polańska, Adriana; Olek‐Hrab, Karolina; Sadowska‐Przytocka, Anna; Żaba, Ryszard; Jenerowicz, Dorota
Abstract The development of an adverse graft‐versus‐host disease (GvHD) is a major complication of stem cell transplantations, which are widely used to cure increasing number of hematologic malignancies. Patients with chronic GvHD are at risk of joint contractures secondary to sclerodermatous skin changes. Several clinical scores or serologic markers have been used to assess skin sclerosis in scleroderma patients. Evaluation of sclerotic skin changes using biometric tools remains to be challenging. The purpose of this study was to illustrate and exemplify ultrasound measurement and measurement of skin elasticity of five chronic sclerodermoid GvHD patients. There is still a substantial lack of studies using objective and non‐invasive methods helpful in assessment of patients with skin involvement of GvHD. Although ultrasound is not the ideal method, it is worth emphasizing that it is still useful, non‐invasive, and repeatable device in monitoring patients suffering from GvHD. It should also be added, that it seems to be advisable to repeat USG examination at an interval of 3 months after the treatment. In addition, skin echogenicity may be a more sensitive parameter than skin thickness in assessment of cGvHD patients.